Gestational Diabetes Mellitus Worsens the Profile of Cardiometabolic Risk Markers and Decrease Indexes of Beta-Cell Function Independently of Insulin Resistance in Nondiabetic Women with a Parental History of Type 2 Diabetes - Alina Sokup; Barbara Ruszkowska-Ciastek; Małgorzata Walentowicz-Sadłecka; Marek Grabiec; Danuta Rość (Journal of Diabetes Research, 2014)
Background. Women with a history of both parental type 2 diabetes (pt2DM) and previous gestational diabetes (pGDM) represent a group at high risk of cardiovascular events. We hypothesized that pGDM changes cardiometabolic risk markers levels as well as theirs associations with glucose indices in nondiabetic pt2DM women. Methods. Anthropometric parameters, glucose regulation (OGTT), insulin resistance (HOMA-IR), beta-cell function, lipid levels, parameters of endothelial dysfunction, and inflammation were evaluated in 55 women with pt2DM, 40 with both pt2DM and pGDM 2–24 months postpartum, and 35 controls. Results. Prediabetes was diagnosed more frequently in women with both pt2DM and pGDM in comparison with women with only pt2DM (10 versus 8, P=0.04). The pGDM group had higher LDL-cholesterol, sICAM-1, tPa Ag, fibrinogen, and lower beta-cell function after adjustment for HOMA-IR, in comparison with pt2DM group. In pt2DM group postchallenge glucose correlated independently with hsCRP and in pGDM group fasting glucose with HOMA-IR. Conclusions. pGDM exerts a combined effect on cardiometabolic risk markers in women with pt2DM. In these women higher LDL-cholesterol, fibrinogen, sICAM-1, tPa Ag levels and decreased beta cell function are associated with pGDM independently of HOMA-IR index value. Fasting glucose is an important cardiometabolic risk marker and is independently associated with HOMA-IR.